2022
DOI: 10.3390/agronomy12112670
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Winter Cover Crops on Maize Yield and Crop Performance in Semiarid Conditions—Artificial Neural Network Approach

Bojan Vojnov,
Goran Jaćimović,
Srđan Šeremešić
et al.

Abstract: Maize is the most widespread and, along with wheat, the most important staple crop in the Republic of Serbia, which is of great significance for ensuring national food security. With the increasing demand for food and forage, intensive agricultural practices have been adopted in the maize production systems. In this direction, considerable research efforts have been made to examine the effects of different types of cover crops as a green manure on maize productivity; however, no consistent conclusions have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In addition, the coefficients linked to the output layer were amalgamated into matrices W 2 and B 2 (Eq. 15) (Vojnov et al 2022):…”
Section: Assessment Of the Impact Of Landfill Size Municipality Size ...mentioning
confidence: 99%
“…In addition, the coefficients linked to the output layer were amalgamated into matrices W 2 and B 2 (Eq. 15) (Vojnov et al 2022):…”
Section: Assessment Of the Impact Of Landfill Size Municipality Size ...mentioning
confidence: 99%
“…Our studies show that precipitation during the growing season is the most important determinant of biomass, which is in agreement with Talgre's [48] finding that the biomass formation and nutrient uptake of leguminous green manure plants, including common vetch, in continental climates is highly dependent on climatic conditions and the length of the growing season. Rainfall during the growing season not only had a significant effect on the biomass yield of green manure, but also influenced corn yield in the years studied [49]. Based on the correlation analyses carried out, it is evident that within the autumn precipitation, the rainfall in October had the greatest influence on the biomass yield.…”
Section: Effects Of Precipitation and Different Seed Densities On The...mentioning
confidence: 81%
“…They also conducted in-depth studies on the state of soil moisture and changes in its amount, considering the consumption of fodder crops. The assessment of the economic and bioenergetic efficiency of the main elements of the cultivation technology (sowing time and mowing time) showed that for obtaining hay from annual fodder sole crops and their mixtures, the most effective elements are an early sowing time (the third 10-day period of May), with a profitability of 176% and energy efficiency of 3.8, and late mowing time, with a profitability of 189% and energy efficiency of 3.5 [49,50].…”
Section: Discussionmentioning
confidence: 99%